Psychological detachment: A creativity perspective on the link between intrinsic motivation and employee engagement. Issue 9 (4th March 2020) - Ghosh, Debjani; Sekiguchi, Tomoki; Fujimoto, Yuka
Abstract : Purpose: The purpose of this paper is to develop an additional perspective on when and why intrinsic motivation predicts employee engagement by presenting a contextual boundary of psychological detachment in relation to the relationship between intrinsic motivation, employee creativity and employee engagement of workers. Design/methodology/approach: Data were collected from 288 full-time Japanese workers using an online survey. The study used a bootstrap method (Preacher and Hayes, 2008) to test mediation, and a Hayes method (2013) to test moderation and a first-stage moderated mediation model. Findings: Employee creativity mediated the relationship between intrinsic motivation and employee engagement, and the relationship between intrinsic motivation and creativity was moderated by psychological detachment. Additionally, the indirect effect of intrinsic motivation on employee engagement via creativity was moderated by psychological detachment. Research limitations/implications: The cross-sectional design may have limited the empirical inferences; however, the proposed model was based on robust theoretical contentions, and the study included an unrelated "marker variable" (neuroticism) as an effective means of identifying common method variance (CMV), thus mitigating the limitation of the design. Practical implications: This study has shown that intrinsically motivated employees who practice psychological detachment from work achieve higher creativity and stronger employee engagement. Originality/value: Based on the unconscious thought theory (UTT), job demand resource theory (JD-R), recovery processes (i.e. effort-recovery model) and self-determination theory (SDT), this paper adds to the literature by demonstrating the mediating and moderating mechanisms driving intrinsic motivation and employee engagement relationship.